2017
DOI: 10.3892/ol.2017.7567
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolism-associated genes and pathways involved in different stages of clear cell renal cell carcinoma

Abstract: The lack of early diagnostic markers and novel therapeutic targets for clear cell renal cell carcinoma (ccRCC) negatively affects patient prognosis. Cancer metabolism is an attractive area for the understanding of the molecular mechanism of carcinogenesis. The present study attempted to identify metabolic changes from the view of the expression of metabolism-associated genes between control samples and those of ccRCC at different disease stages. Data concerning ccRCC gene expression obtained by RNA-sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The same study found that genes associated with metabolic damage may also affect the prognosis of patients. Our previous research suggests key metabolic genes play crucial roles in kidney cancer [21] and liver cancer [22]. In the present study, we revealed gender-specific metabolic changes in LUAD patients.…”
Section: Discussionsupporting
confidence: 62%
“…The same study found that genes associated with metabolic damage may also affect the prognosis of patients. Our previous research suggests key metabolic genes play crucial roles in kidney cancer [21] and liver cancer [22]. In the present study, we revealed gender-specific metabolic changes in LUAD patients.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, HIF-1α increased the expression level of GLUT-1, which promoted cellular glucose uptake in VHL-deficient ccRCC and further induced angiogenesis [66]. Amino acid metabolism has also been reported to participate in ccRCC tumorigenesis [67–69]. Tryptophan was increasingly used in ccRCC cells, which enhanced tumor growth and further resulted in immunosuppression with low efficiency of interferon-α immunotherapy [70].…”
Section: Discussionmentioning
confidence: 99%
“… 8 According to multiple reports, cellular metabolism is intricately involved with numerous signal transduction pathways and plays an essential role in several disease states. 9 , 10 Consequently, blocking the implicated metabolic pathways can sometimes prove to be an effective treatment strategy. 11 Several studies have found associations between the pathogenesis, metabolism and management of DLBCL.…”
Section: Introductionmentioning
confidence: 99%